Young people's mental health: the spiritual power of fairy stories, myths and legends - Walker, Steven (Mental health, religion & culture, 2010)
Children and young people have the capacity to conjure feelings of faith and hope when experiencing emotional and psychological distress. World myths, legends and fairy stories as part of early child development offer a rich source of material to draw from and enlist in the therapeutic endeavour. Fairies often act in a healing capacity in mythology, or they appear as agents between the world of human affairs and the invisible forces of nature. Mythological beings also possess helping powers in advance of mortals achieving superhuman tasks, but they can also when used as metaphor, frighten children and potentially cause psychological harm. This paper suggests that mental health practitioners can utilise such powerful narratives therapeutically and in a culturally respectful and spiritually innovative way. Harnessing the child's imagination can be a powerful vehicle for a transforming experience at the psychic level with consequent positive benefits for emotional well-being.